Waste Not, Grow A Lot:: Coffee Grounds and Sustainable Farming - Lachica, Jehan Grace M.; Salic, Merhama T.; Marabong, Shannel S.; Mala-amama, Almerah A.; Campong, Jehanne A.; Dimangadap, Shaihanie M. (SEAMEO BIOTROP, 2025)
Coffee is a daily favorite beverage for many Filipinos, but once the brew is done, the leftover grounds—known as spent coffee grounds (SCGs)—are usually tossed out. What most people don’t realize is that these leftover grounds are packed with nutrients that can actually benefit our soil and boost plant growth. We tested discarded Robusta SCGs, both in their raw and burnt forms. It turned out that the SCGs could be used as organic fertilizers for tomato plants. How so?